Pengembangan Media Pembelajaran Addie Terhadap Pemahaman Konsep Matematika Dan Keterampilan Berpikir Kritis Siswa Kelas X SMKN 25 Jakarta - Astri Astuti; Adib Rozan; Nissa Nur Fadillah; Nisvi Nur Sya’bania (Pendekar : Jurnal Pendidikan Berkarakter, 2024)
This research This research aims to determine the feasibility, practicality and effectiveness of ADDIE learning media in the form of SPLTV boards in improving the ability to understand mathematical concepts and critical thinking skills of students at SMKN 25 Jakarta. This research adopts the ADDIE model stages (analyze, design, develop, implement, and evaluate). The analyze stage includes initial analysis, student analysis, concept analysis and formulating learning objectives. The design stage includes preparing learning media in the form of selecting appropriate media and designing learning content. The development stage includes the development of data collection instruments. The data collection instrument in this research was interviews with the teachers concerned. The implementation stage includes the application of ADDIE learning media which has been developed for class X students at SMKN 25 Jakarta. The evaluation stage includes the form of evaluation carried out at each ADDIE stage. The data analysis technique used is the validity coefficient by Aiken's V The research results show that the ADDIE learning media in the form of the SPLTV board developed is suitable for use in Mathematics learning. The SPLTV board is practical to use and effective in improving students' concept understanding and critical thinking abilities.